2021
DOI: 10.9740/mhc.2021.07.243
|View full text |Cite
|
Sign up to set email alerts
|

Hyperammonemia in patients receiving valproic acid in the hospital setting: A retrospective review

Abstract: Introduction Valproic acid (VPA) is widely used for the treatment of epilepsy, migraine, and a variety of psychiatric conditions. The reported incidences of hyperammonemia induced by VPA use is variable. The purpose of this study is to evaluate the incidence of VPA-induced hyperammonemia in the general adult inpatient population. Methods Adult patients who received at least 1 dose of VPA and derivatives between June 1, 2017 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Manual search of reference lists and gray literature did not identify additional studies. After screening and assessing for eligibility, 240 studies were included with the remaining articles being excluded for meeting the exclusion criteria 6,7,12–245 . Among the excluded 350 articles, 37 were literature reviews, 5 were pharmacokinetically related, 41 were VPA overdose related, and 267 articles were unable to clearly answer our objectives listed.…”
Section: Resultsmentioning
confidence: 99%
“…Manual search of reference lists and gray literature did not identify additional studies. After screening and assessing for eligibility, 240 studies were included with the remaining articles being excluded for meeting the exclusion criteria 6,7,12–245 . Among the excluded 350 articles, 37 were literature reviews, 5 were pharmacokinetically related, 41 were VPA overdose related, and 267 articles were unable to clearly answer our objectives listed.…”
Section: Resultsmentioning
confidence: 99%
“…One of the patients of our study was under valproic acid therapy before the diagnosis. Valproic acid induces hyperammonemia as documented in several case reports (Aiyer et al, 2016; McMorris et al, 2021), exacerbating hyperammonemic crises present in UCD and triggering HE (Wu et al, 2021); therefore, its use must be immediately revised. In addition, it is essential to monitor frequent ammonia levels in patients presenting hyperammonemia and HE in use of valproic acid or sodium valproate, to unmask an underlying error of metabolism, such as UCD (Mehta et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…VPA can affect liver and kidney metabolism, resulting in decreased ammonia clearance. Studies have shown that 20.4% of general hospitalized adults receiving VPA develop hyperammonemia 71 . In some cases, hyperammonemia led to severe hyperammonemic encephalopathy 72 .…”
Section: Application Of Pd In Nervous System Diseasesmentioning
confidence: 99%